Kontribusi Kepemimpinan Kepala Sekolah Dalam Menciptakan Iklim Kelas Yang Kondusif Di SMP Muhammadiyah Sumbang Kecamatan Sumbang Kabupaten Banyumas - Teguh Dasa Prianto (QALAM: JURNAL PENDIDIKAN ISLAM, 2021)
This study aims to: determine the contribution of the principal's leadership in creating a classroom climate that is conducive in SMP Muhammadiyah Contribute, Contribute subdistrict, Banyumas, through the role that principals namely, (1) the role of the principal as an educator. (2) the role of the principal as the manager, (3) the role of the principal as an administrator, (4) the role of the principal as a supervisor. The method used in this research is descriptive qualitative method. Data collection techniques in this study in two ways, namely through the collection of secondary data and primary data. Then the data analysis technique used in this research is data triangulation technique that consists of observation, interviews, and documentation. From the research results can be seen that the contribution of the principal's leadership in creating a classroom climate that is conducive to say very good contribution. However, in a supervisory role still needs to be improved to maximize this case related to the discipline of teachers and students who have not been so maximum. Some of the factors that constrain the principal in creating a conducive classroom climate that is the level of awareness and mindset of teachers and learners who have not changed, still using the old patterns. To overcome these obstacles principals should further improve the supervisory function. Principals should be focused on improving the supervision of the learning process, by carrying out regular supervision of the overall learning process in schools actively, so that the principal contribution to climate conducive grade can be guaranteed.